The Release of Diazepam from Different Conventional and Hollow Type Suppository Bases - Balkis A. Kamal (College of Pharmacy University of Baghdad, 2017)
The objective of this study was to investigate the release profile of different fat and water soluble bases using diazepam as a model drug , and then to develop  a satisfactory formula with a rapid release of diazepam from suppository bases .The study was conducted using theobroma oil ,glycerol-gelatin and glycerol-PEG1540 bases using conventional mold method for preparation .while the later base was utilized to incorporate diazepam ( buffered solution ) in a hollow type suppositories. The results indicated that all types of bases can be utilized to formulate diazepam as  rectal suppositories with acceptable disintegration time ( 12, 10, 6, and 6min.), respectively . While 100% of the  released drug had been shown different release profiles with different storage time ( 15, 30, and 45 days ) in a refrigerator at 5Â°C , best results were obtained , when glycerol- PEG1540 used as a base for both conventional and hollow type mold methods .However , a decrease in the release rate of the drug was seen with glycerol-gelatin and glycerol-PEG1540 and to a lesser extent for glycerol-PEG1540 prepared by hollow type method . Key words:  Diazepam  , Hollow type suppository